A study on the actual state of utilization by national registered dietitians of information related to assessment items of nursing care intensity - Otaga, Masaaki; Tsutsui, Takako; Nishii, Mizuho (Journal of Japan Society for Nursing Administration and Management, 2019)
This study was aimed at clarifying the awareness in national registered dietitians of nursing care intensity items, and current practice relating to these items, and at examining ways to contribute to the promotion of multi-occupational collaboration. A self-administered questionnaire survey was conducted for 33 national registered dietitians working in four acute care hospitals. Responses were obtained from 25 subjects (response rate, 75.8%). Results showed that ″None″ of all 25 subjects had experience of participating in an in-hospital training course related to nursing care intensity items. Subjects who had ever checked the nursing care intensity evaluation items and information related to these items in nutritional practice numbered 15, and 10 had never checked them. In addition, we looked at whether the evaluation item ″Evaluation form on the severity and the necessity of medical care / nursing I for general ward″ was used in the practice of nutritional care with hospitalized patients, and rated the frequency of use using the 5-point Likert scale. Results showed that patient information utilized for nutritional care included ″status of meal intake assistance″, ″treatment with an antineoplastic agent″, ″presence of a pressure sore″,″presence of radiation treatment″, ″communicability of instructions from staff on medical treatment/ care of the patient″, and other factors. It was suggested that information on nursing care　intensity　items could be used for nutritional management work as well. However, it is necessary to provide education and training related to nursing care intensity items for occupations in which multi-occupational collaboration has not yet been promoted, so that nutritionists use information on nursing care intensity evaluation, and practice hands-on in-hospital care as members of a multi-occupational team.